Efeito de sistemas de resfriamento sobre as variáveis termofisiológicas, hormônios tireoidianos e desempenho de porcas lactantes - Rigo, Evandro José (2018)
In the first study, the effects of the housing of lactating swine matrices in different positions in a shed with negative pressure evaporative cooling system (ECS) on the physiological parameters of thermoregulation, productive and reproductive performance in the summer were determined. 34 females, randomly chosen from the three lines of cages, were used in the positions: near the pad cooling; in the middle of the shed and near to the exhaust fans. The air temperature (Ta) and the temperature and humidity index (THI) were lower near the pad cooling (22.38 ºC, 71.84, p<0.05) than the middle (24.56 ºC, P <0.05) and near the exhaust fans (25.00 ºC, 75.62, p<0.05). Respiratory frequency, rectal and suface temperatures were lower in the sows near the pad cooling (43.67 breaths.min-1, 38,40 ºC, 29,51 ºC, p <0,05) in relation to the middle animals (52.04 breaths.min-1; 38.48 ºC; 32.02 ºC, p <0.05) and near the exhaust fans (56.38 breaths.min-1, 38.93 °C, 32.52 ° C, p <0.05). The backfat thickness, the weaning-estrus interval and daily average consumption of the sows, number of weaning piglets, corporal mass and daily average gain of the piglets were not influenced by the position of housing in the shed. Lactating sows housed in the middle and near to the exhaust fans in the ECS present higher thermoregulation physiological variables, however with no impairment their performance. In the second study the effects of evaporative cooling with negative pressure (ECS) and water spray on the roof (WOR) on the physiological variables, thyroid hormones and neutrophil/ lymphocyte ratio in lactating sows were evaluated. 30 females, hybrid, under ECS and 31 in WOR, randomly chosen from cage lines, were used in the summer. The thermal environment, respiratory rate (RF), surface temperatures (ST) and rectal (RT), serum thyroxine and triiodothyronine concentration, number of neutrophils and lymphocytes and the neutrophil/ lymphocyte ratio were determined. In the afternoon, matrices in ECS (Ta: 25.0 °C and THI: 74.7) and WOR (Ta: 27.6 °C and THI: 77.3) were exposed to heat stress. In the morning, RF, ST and RT were lower in ECS (48.6 breaths.min-1, 31.1 °C and 38.5 °C, respectively) than WOR (54.4 breaths.min-1, 32.8 °C and 38.6, respectively), and also the afternoon ECS (54.6 breaths.min-1, 30.3 °C and 38.8 ° C, respectively) and WOR (65.5 breaths.min-1, 31.4 °C and 39.1 °C, respectively). The neutrophil/lymphocyte ratio, serum concentration of T3, free T4 and T4/T3 ratio were not influenced by the cooling system. Lactating sows raised in ECS sheds are easier to maintain homeothermia than those maintained under WOR in the summer in a tropical environment